EMU: A giant with feet of clay? - Carmen Dolores Wehbe Herrera (European Regional Science Association (ERSA), 1998)
Right from the beginning, the process of European integration has been influenced by the events of the international scene.This is why the memebers of the European Community soon raised the possibility of creating and consolidating a zone of monetary stability,protected from the vicissitudes of the International Monetary System. After more than twenty years of pursuing this goal,the Treaty of Maastricht included Monetary Union as a priority objective for the European Union. However, the fact that we are currently immersed in the process of Monetary Union has meant that the Union has had to put other fundamental aspect of consolidating and strengthening overall integration on the back burner. What is more,if these latter aspect are not given the importance they deserve and are not treated at a suitable level, the whole unique project of co-operation between national states could be put in jeopardy. The aim of this paper is to provide a more detailed review of the increasingly evident cracks that are appearing in the process of European integration, cracks that have been highlighted by the advance toward Monetary Union. The review is based on a study of the evolution and the influence international events have had on the different monetary aspects that have been addressed by the European Union, on the one hand, and an analysis of the main features of Monetary Union,on the other. Finally,we address the criticism and shortcomings of a process which, in its current fundamental guise,leads us to wonder if we are dealing with a giant with feet of clay, an economic giant but a political dwarf.
Keywords: 330